ANALISIS KOMPETENSI LULUSAN SMK YANG DIBUTUHKAN DU/DI DENGAN METODE MULTIPLE CRITERIA UTILITY ASSESMENT (MCUA) - Hendro, Hendro; Vontas Alfenny; rahmat, hudan (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
Abstract: The purpose of this study is to determine the competency of SMK graduates with Dudi competence (Business World/Industry World). There is still a gap between the skills possessed by vocational high school graduates and the needs of the business and industry world. This is due to the mismatch between the competencies taught in education and the existing technological developments. Multiple Criteria Utility Assessment (MCUA) is a method used in decision-making that involves multiple criteria or factors that need to be evaluated. This method helps in selecting the best alternative based on objective assessments of various relevant factors. It involves collecting data on criteria relevant to decision-making and then assigning weights or importance to each criterion. Then, each alternative is evaluated based on these criteria, and a value or score is given for each alternative on each criterion. These scores are then used to calculate the utility value for each alternative. The results obtained show that Problem A, which is communication skills with a total value of 165 after being multiplied by the weight, becomes the first priority for improvement. Problem B, management skills, has a total value of 155, making it the third priority for improvement. The total value of 155 becomes the second priority for improvement. Overall, it is necessary to design an integrated and sustainable program in schools or educational institutions to enhance students' communication, planning and organizational skills, as well as their management abilities. Collaboration with industries and the implementation of active and project-based teaching methods can provide practical experiences to students. It is also important to involve experts and industry practitioners in designing programs that are relevant to the current job market needs.